2016
DOI: 10.1016/j.janxdis.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and racial differences in clinically relevant symptoms in active duty military personnel with posttraumatic stress disorder

Abstract: Previous research has shown racial/ethnic differences in Vietnam veterans on symptoms related to posttraumatic stress disorder (PTSD). The current study explored racial/ethnic differences in PTSD symptoms and clinically relevant symptoms. Resilience and social support were tested as potential moderators of racial/ethnic differences in symptoms. The sample included 303 active duty male service members seeking treatment for PTSD. After controlling for age, education, military grade, and combat exposure, Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…Interestingly, there were no racial differences in trauma. Together these findings add to other studies reporting greater PTSD symptoms in Black compared to White women (e.g., Brewin et al, 2000; Frueh et al, 1998; Kaczkurkin et al, 2016). As Black men and women are less likely to seek psychological treatment compared to their White counterparts, potential racial differences in the incidence and severity of PTSD symptoms could have far-reaching clinical consequences (e.g., Roberts et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, there were no racial differences in trauma. Together these findings add to other studies reporting greater PTSD symptoms in Black compared to White women (e.g., Brewin et al, 2000; Frueh et al, 1998; Kaczkurkin et al, 2016). As Black men and women are less likely to seek psychological treatment compared to their White counterparts, potential racial differences in the incidence and severity of PTSD symptoms could have far-reaching clinical consequences (e.g., Roberts et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Pervasive exposure to racial discrimination has been proposed as a potential mechanism or explanation regarding why Black Americans are at an increased risk of PTSD. Indeed, racial discrimination has been documented as a significant contributor to psychological sequelae in this population following trauma exposure (Kaczkurkin et al., 2016; Sibrava et al., 2019).…”
mentioning
confidence: 99%
“…Future research should use longitudinal designs to assess changes of these emotional responses over time and after successful PTSD treatment. In addition, previous research has indicated that trauma exposure (e.g., time since trauma) and demographic characteristics are associated with PTSD symptoms (e.g., Kaczkurkin et al., ). These factors should also be taken into account in future studies to understand the negative emotional response to trauma.…”
Section: Discussionmentioning
confidence: 99%